Syndrome resembling Kawasaki disease in COVID-19 asymptomatic children (2020)
The current knowledge about the COVID-19 (Coronavirus Disease-2019) pandemic is still limited and is unravelling with the passing days, especially clinical data, and research in pediatric age group. Recently, there is a new and crucial development reported recently among the COVID-19 asymptomatic children, a novel syndrome affecting asymptomatic COVID-19 children, presenting as a hyperinflammatory syndrome which is like Kawasaki disease shock syndrome. The purpose of this correspondence is to discuss some important findings of the syndrome for the better understanding of the disease.